Estimation of Crystallite Size, Lattice strain and Micro Residual Stresses by FWHM method and impact of Feed rates on Residual stresses. Issue 1 (December 2020) - Kumar, Aneesh
Abstract: The prediction and control of residual stresses of machined components is necessary. The tribological properties such as wear and tear are get influenced by it. The analytical assessment of residual stress profile of mechanically micro machined specimen with XRD (X Ray diffraction) technique are proposed. Also the lattice strain and crystallite sizes for different specimens were assessed. Residual stresses and feed rates are found significantly correlated and gets affected for Low Carbon Steel Specimensduring micro milling.